Evaluation of foreign apricot cultivars in Hungary - Szalay, L.; Balázs, G.; Nagy, P. (International Journal of Horticultural Science, 2004)
The extension and renewal of cultivar assortment is one of the key elements in the improvement of apricot production. Competitiveness can only be achieved by planting cultivars which meet all market requirements and yield reliably under the environmental conditions of the given production site. Beside breeding programmes, the range of cultivars can also be extended by the domestication of foreign cultivars. Most apricot cultivars have low ecological tolerance, therefore, cultivars improved or developed in other countries should only be involved in production after due consideration. The suitability of such cultivars has to be examined for several years. Foreign apricot cultivars have been tested in our cultivar collection for over 10 years. Hereby, the most important aspects of market value and the adaptability to the environmental conditions of the production site are demonstrated. According to the results of our examinations the production of early ripening ’Orange Red’ and `Goldrich’ can be promising in Hungary. From cultivars ripening in the peak season only those are expected to be widely produced which differ from Hungarian cultivars or surplus them in some respects. From the cultivars examined ’Harogem’ which ripens at the same time as `Gönci magyar kajszi’ has remarkably aesthetic fruits with glossy surface, while the large fruits of `Hargrand’ has firm pulp. Late ripening cultivars have significant importance in the northern border of production. According to our examinations the cultivars ’Callatis’, `Comandor and `Sirena’ are applicable in Hungary to extend the harvesting season.